Gravitation, inertia and weightlessness : centrifugal and gyroscopic effects of the n-body system's interaction energy /: centrifugal and gyroscopic effects of the n-body system's interaction energy. (2016) - Ferronskiĭ, V. I (Vasiliĭ Ivanovich)
No abstract available